2021
DOI: 10.1038/s41598-021-02242-x
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 ectodomain is a flagellin-targeting decoy receptor and biomarker operative during Pseudomonas aeruginosa lung infection

Abstract: We previously reported that flagellin-expressing Pseudomonas aeruginosa (Pa) provokes NEU1 sialidase-mediated MUC1 ectodomain (MUC1-ED) desialylation and MUC1-ED shedding from murine lungs in vivo. Here, we asked whether Pa in the lungs of patients with ventilator-associated pneumonia might also increase MUC1-ED shedding. The levels of MUC1-ED and Pa-expressed flagellin were dramatically elevated in bronchoalveolar lavage fluid (BALF) harvested from Pa-infected patients, and each flagellin level, in turn, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…3b ). It has been reported that MUC1, an O-glycosylated membrane-tethered mucin on cancer cells, interacts with P. aeruginosa through flagellin 44 , 45 . Muc1 ‒/‒ animals displayed ~50% less adherence of P. aeruginosa in the lungs compared with Muc1 +/+ mice 46 .…”
Section: Resultsmentioning
confidence: 99%
“…3b ). It has been reported that MUC1, an O-glycosylated membrane-tethered mucin on cancer cells, interacts with P. aeruginosa through flagellin 44 , 45 . Muc1 ‒/‒ animals displayed ~50% less adherence of P. aeruginosa in the lungs compared with Muc1 +/+ mice 46 .…”
Section: Resultsmentioning
confidence: 99%
“…MUC1 expression also influences a variety of other human bacterial infections, including those by E. coli , S. enterica Typhimurium, S. pneumoniae , Staphylococcus aureus , Bacillus subtilis , Campylobacter jejuni , and Haemophilus influenzae ( 257 – 267 ). Based on these studies and the documented role of the NEU1 – MUC1 axis in regulating airway inflammation in response to P. aeruginosa ( 40 , 49 , 51 , 232 ), it is likely that this same pathway impacts the interaction of a broad array of pathogenic microorganisms with the human host. In summary, these collective studies suggest that NEUs and MUCs play important roles in regulating bacterial infections.…”
Section: Neus and Mucs In Infectious Diseasesmentioning
confidence: 99%
“…To extend these results to an in vivo human setting, studies were conducted to determine whether shed MUC1-ED levels might be elevated in BALF of patients with P. aeruginosa lung infection, and whether the recombinant MUC1-ED protein might influence in vitro parameters of the host proinflammatory response to bacterial infection ( 232 ). BALF from patients with P. aeruginosa pneumonia contained higher levels of MUC1-ED, compared with either BALF from noninfected patients or patients infected with microorganisms other than P. aeruginosa , and shed MUC1-ED in the BALF of P. aeruginosa -infected patients was desialylated, presumably from the action of NEU1.…”
Section: Neus and Mucs In Infectious Diseasesmentioning
confidence: 99%
“…Subsequently, they also verified that Neu1 provoked the shedding of MUC1-ED from airway, which suppressed Pa lung infection in BALB/c mice [ 9 ]. Recently, Simeon’ team reported that the concentration of desialylated MUC1-ED and flagellin expression in Pa were dramatically increased in bronchoalveolar lavage fluid (BALF) harvested from Pa-infected patients [ 10 ], this indicated that measurement of MUC1-ED in BALF levels might serve as a guide for antibiotic therapy in patients with Pa-infections. In summary, different in vivo experiments confirmed that NEU1 might modulate the desialylation of human ECs receptors to resist the pulmonary bacterial infections.…”
Section: Neu1 and Lung Injurymentioning
confidence: 99%
“…Previously, much attention has been paid to the role of Neu1from viral and bacterial in human respiratory diseases. In recent years, there has been growing interest in the role of human Neuraminidases 1 (Neu1), a sialidase enzyme, in the development and progression of respiratory diseases [ 1 10 ].…”
Section: Introductionmentioning
confidence: 99%